2019
DOI: 10.1007/s12652-019-01290-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactive spaces for children: gesture elicitation for controlling ground mini-robots

Abstract: Interactive spaces for education are emerging as a mechanism for fostering children's natural ways of learning by means of play and exploration in physical spaces. The advanced interactive modalities and devices for such environments need to be both motivating and intuitive for children. Among the wide variety of interactive mechanisms, robots have been a popular research topic in the context of educational tools due to their attractiveness for children. However, few studies have focused on how children would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In another case [14] the interaction of children was analyzed with the help of gestures that showed a good percentage of acceptance of the new means of communication. The children were found to have great motivation for the activity and the ease of interaction was assessed as very positive [9]. The work of Nacher, Garcia-Sanjuan and Jaen showed that in young children and around the age of 6, it is difficult to interact with mechatronic systems.…”
Section: State Of the Artmentioning
confidence: 99%
“…In another case [14] the interaction of children was analyzed with the help of gestures that showed a good percentage of acceptance of the new means of communication. The children were found to have great motivation for the activity and the ease of interaction was assessed as very positive [9]. The work of Nacher, Garcia-Sanjuan and Jaen showed that in young children and around the age of 6, it is difficult to interact with mechatronic systems.…”
Section: State Of the Artmentioning
confidence: 99%
“…4.2 below. This method has been used in many elicitation studies focusing on gesture elicitation in particular [1,6,10,11,17,36,38,40,44,45,53], and was our method of choice due to the similarity of gestures and sketches for expressing commands, as discussed in Sect. 2.4.…”
Section: Elicitation Studymentioning
confidence: 99%
“…Consequently, many studies have proposed approaches to reduce robot control mental workloads using NUIs [11][12][13]. Various NUI approaches have suggested robot control interfaces that are easier to understand and learn [14][15][16][17], and have focused on improving the robot control experience and usability [18][19][20][21]. Therefore drone control interfaces that are closer to natural human behaviour will improve mental workload, learnability, and usability.…”
Section: Introductionmentioning
confidence: 99%